CT Imaging and Differential Diagnosis of COVID-19. Issue 2 (May 2020) - Dai, Wei-cai; Zhang, Han-wen; Yu, Juan; Xu, Hua-jian; Chen, Huan; Luo, Si-ping; Zhang, Hong; Liang, Li-hong; Wu, Xiao-liu; Lei, Yi; Lin, Fan
Since the beginning of 2020, coronavirus disease 2019 (COVID-19) has spread throughout China. This study explains the findings from lung computed tomography images of some patients with COVID-19 treated in this medical institution and discusses the difference between COVID-19 and other lung diseases.